Fatty acid and chemical composition of the seed and the oil obtained from marolo fruit (Annona crassiflora Mart.) (Research, Society and Development, 2020)
The addition of values to native fruits through studies that enable the various ways of harnessing them becomes an important strategy in the preservation process. In this sense the objective of this study was the physical and chemical characterization of the seed (peel, seeds, and pulp) as well as its oil derived from marolo fruit (Annona crassiflora Mart.) The analyses proximate composition, pH, titratable acidity, antioxidant activity, vitamin C concentration, total carotenoids, β–carotenes, iodine index, peroxide index, refraction, saponification, saponifiable matter, fatty acid profile, water activity, color, and rheology were studied. The peel of marolo seed was proved to be rich in carbohydrates, antioxidant substances and vitamin C. The seeds, in turn, presented high content of lipid, proteins and vitamin C. The oil extracted from marolo seed presented low refraction index, peroxides index, and unsaponifiable matter, besides a high content of vitamin C and unsaturated fatty acid compared with soybean oil, in addition to the presence of antioxidant compounds. Through the study, the feasibility of using by-products from processing of marolo seeds as a source of oils with high nutritional content was concluded.